2021
DOI: 10.1080/07853890.2021.1981548
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of standardised fruit extract of Garcinia cowa Roxb. ex Choisy against ethanol induced gastric mucosal lesions in Wistar rats

Abstract: Background and aim The fruit of Garcinia is a rich and valuable source of bioactive compounds and is traditionally used for treating wounds and ulcers. The present study was carried out to investigate the protective effect of chromatographically standardized fruit extract of Garcinia cowa (GCE) on ethanol-induced gastric lesions in rats and its possible mechanisms. Methods The effect of GCE (200 and 400 mg/kg body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In addition, the contents of piperine and piperidine were identified as 23.54% and 4.43% respectively, which were proved to be anti-inflammatory and antioxidant components in PLL and ginger [ 45 , 46 ]. Gupta et al showed that gallic acid had antiulcer effects through antioxidation, and the results of this study showed that the content of gallic acid in MD-4 was 12.02% [ 47 ]. The findings of this study thus support the above studies by suggesting that the compounds present in MD-4 could display protective effects mainly by modulating inflammatory and antioxidant mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the contents of piperine and piperidine were identified as 23.54% and 4.43% respectively, which were proved to be anti-inflammatory and antioxidant components in PLL and ginger [ 45 , 46 ]. Gupta et al showed that gallic acid had antiulcer effects through antioxidation, and the results of this study showed that the content of gallic acid in MD-4 was 12.02% [ 47 ]. The findings of this study thus support the above studies by suggesting that the compounds present in MD-4 could display protective effects mainly by modulating inflammatory and antioxidant mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be assumed that N. sativa seed from Saudi Arabia have a high gastroprotective effect in the ethanol-induced gastric ulcer rat model. Several studies have shown that stimulated production of gastric wall mucus and reduced gastric acidity prevent ethanol-induced gastric ulcers [ 14 , 15 , 16 , 17 ]. It was hypothesized that BSO can effectively reduce the gastric ulcer area by stimulating the production of gastric wall mucus and suppressing gastric acidity, compared with the control pretreatment (distilled water).…”
Section: Discussionmentioning
confidence: 99%
“…NP-SH plays an important role in tissue protection by scavenging prooxidants, endogenous NP-SH complex is a major component in mucosal protection against ethanol-induced stomach damage [60]. Assay results showed that ethanol significantly decreased gastric mucosal NP-SH level compared to the control group (P < 0.01).…”
Section: Effect Of Doff On Ethanol-induced Mucosal Np-sh Depletionmentioning
confidence: 95%